POTENSI PENINGKATAN PENYERAPAN KARBON DI PERKEBUNAN KARET SEMBAWA, SUMATRA SELATAN - Charlos Togi Stevanus; Sahuri Sahuri (Pusbindiklat - LIPI, 2014)
Addition to its economic contribution, rubber plantation plays an important role in sequestration of carbon. Carbon sequestration of rubber plantation could be increased through the application of intercropping system with high biomass timber trees. This study aimed: 1) to asses the potential increase of land carbon stock in rubber plantation intercropped with teak (Tectona grandis) and trembesi (Samanea saman); and 2) to examine theroleofforestryplantsintercroppingonrubbertreesasanalternativetoreduceCO2 emissions.Theresearch was conducted at the Balai Penelitian Sembawa’s plantation, South Sumatera, with three intercropping patterns, namelyPT1:teak+rubberplants,PT2:trembesi+rubberplants,andPT3:rubbertreemonocultures.Carbon stocks measurement is divided into three components: living part (tree biomass), dead part (necromass) and soil (soil organic matter). The results showed that the highest value per hectare of tree biomass, litter and soil carbon wasatPT2experimentwhilethelowestwasatPT3.TotalCO2 fixationperyearatPT1,PT2,andPT3were 18.54tons/ha,35.69tons/haand32.34ton/ha,respectively.Theincreaseincarbon sequestrationlevelbecause oftheexistenceoftrembesiwas9.3%oraround0.92tonnesC/ha/year,higherthanthatinmonoculturerubber plantation. 2 theroleofforestryplantsintercroppingonrubbertreesasanalternativetoreduceCO